Metabolomic and transcriptomic analysis of the flavonoid biosynthesis pathway in Epimedium sagittatum (Sieb. et Zucc.) Maxim. from distinct locations - Tian, Shuyun; Lv, Xingbin; Li, Mengxue; Tang, Qin; Huang, Huilian; Hu, Shengfu; Li, Fengqin; Xu, Yanqin (Frontiers in Plant Science, 2024)
Epimedium sagittatum (Sieb. et Zucc.) Maxim. (ESM) which accumulates several principal flavonoid compounds including epimedin A, B, C and icariin, is extensively utilized in traditional herbs for sexual dysfunction, osteoporosis etc. In China, ESM has a wealth of wild plant resources and characterized by significant variability in medicinal compounds accumulation. Understanding the diversity of ESMs can lead to better utilization of these plant resources. In this study, we integrated the metabolomic and transcriptomic analysis of three ESMs that originated in Anhui, Hubei and Jiangxi in China. Results showed that the flavonoid biosynthesis as well as the related gene expression in these ESMs revealed substantial differences. For example, the epimedin A, B, C and icariin as well as some related gene expression in ESMs from Anhui are significantly lower than those of in others. These results suggested that the ESMs from wild population without quality checkout may not be suitable for directly use as the materials for preparation of Chinese medicine and ESMs with different accumulation of metabolites could be used for distinct applications.